Low Temperature Influence on Human Placenta Extract Protective Action Towards Erythrocytes Against Oxidative Stress - Narozhnyi, Stanislav V.; Rozanova, Svetlana L. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):174.